Keragaman Genetik 50 Aksesi Plasma Nutfah Kedelai Berdasarkan Sepuluh Penanda Mikrosatelit - Chaerani Chaerani; Nurul Hidayatun; Dwinita Wikan Utami (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2011)
Genetic Diversity of 50 Soybean Accessions Based on TenMicrosatellite Markers. Chaerani, Nurul Hidayatun, andDwinita W. Utami. Soybean accessions in germplasmcollection have increased in number as a result ofexploration, introduction as well as development or releaseof new commercial varieties. This complicates accurate andreliable evaluation of an accession for purposes of utilizationin breeding program and discrimination of a newcommercial variety for purposes of plant variety protection.The aims of this study were to identify the genetic diversityof soybean germplasm to complement the existingphenotypic database as the basis for efficient managementand accurate discrimination of commercial varieties, and toidentify potential parents for hybridizations. Fifty soybeanaccessions consisting of 12 released varieties, 32 localvarieties, and 6 introductions were analyzed usingmicrosatellite DNA markers based on semi-automatic sizingsystem. A total of 86 alleles were detected with the numberof alleles per locus ranged from 4 to 16. Rare alleles weredetected at a rate of 53% which was shown by 68% of thegenotypes. Informativeness of the microsatellite markers asmeasured by the average gene diversity (D) orpolymorphism information content (PIC) was 0.60 and 0.58,respectively. A heterozygosity level of 0.09 as detected byseven loci was observed among 64% of the genotypes. Theaverage genetic distance among the genotypes was 0.56,which indicated the relatively low polymorphism among theanalyzed soybean germplasm. Four microsatellites thatshowed a high D or PIC value (over 0.75) were able todiscriminate between accession reliably. Each soybeanaccession had different DNA microsatellite fingerprint whichcan be used for accurate discrimination to complement theprevious conventional characterizations. UPGMA clusteringseparated the 50 accessions into 10 major clusters, whichshowed no clear pattern of clustering according to varietalgroup or geographical origin. Genetic similarity dataidentified five clusters and 15 genotypes with highest interclusteror inter-genotype genetic distances which arepotential candidates to be exploited as parents inhybridizations for development of new commercial varieties.